FUNCTIONING DISCOURSE MARKERS TO CONSTRUCT A SOCIAL SITUATION IN SPEECH - Jayantini, I Gusti Agung Sri Rwa; Juniartha, I Wayan; Aditana, I Kadek Arya; Umbas, Ronald; Suwastini, Ni Komang Arie (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2021)
This study relates the discussion of discourse markers to their functions from a social context. It aims to identify discourse markers and analyze their function to construct a social situation in Steve Jobs’ speech delivered at Stanford Commencement Address. To analyze the data in this study, the researchers used a qualitative descriptive method. This study showed that the dominant discourse markers used were connective, followed by cause result, temporal adverb, and marker of response, respectively, in which the last marker was the least used. Furthermore, all discourse markers functioned to gain coherent message delivery in the speech by considering the “setting and scene," "participants," "ends,” “act sequence,” “key,” “instrumentalities,” “norms of interaction,” and “genre,” all of which were shortened in the acronym of “speaking.”  Finally, based on its social situation, the present study is expected to broaden the understanding of discourse markers in a particular text.